The Iranian Interventionist Policies in Iraq Between 2003 to 2020 - KAMER, KAIS ABU (İstanbul Kültür Üniversitesi, 2021)
Almost twenty years after the American invasion to Iraq, the country is still in political turmoil. Ethnic and sectarian division opened Iraq to foreign intervention and manipulation. Neighboring countries, other regional and political actors play role in even Iraqi daily affairs. For this reason, the political scene in Iraq seems to be difficult to understand. After the eight year long Iran-Iraq war in 1988 proved a resolved competitor of Iran, Iraq gradually came under the direct influence of Iran, following the US invasion in 2003. This research examines the Iranian foreign policy and the tools Iran had utilized to achieve near complete control over Iraq in the aftermath of the US invasion.
İran'ın 2003 ve 2020 Yılları Arasında Irak'taki Müdahaleci Politikaları
▪ Yüksek lisans tezi.